(untitled) (Revista de Letras Norte@mentos, 2016)
In this article we aimed at establishing, through an interdisciplinary perspective, a dialogue with the areas of Translation, English Language Teaching and Philosophy. Such reflections refer, for the most part, on the empowering process of pre-service English teachers in the acquisitional milieu. Resorting to this understanding, the present article intends to enable the setting of a reflection around the interdependent and constituting relationship among translation activity, learning process and formative experience. Therefore, we search, all along this text, the establishment of key points which help in the understanding of student’s linguistic-communicative development, as well as their movement towards the teaching of this target-language.